2021
DOI: 10.26554/sti.2021.6.4.273-284
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Formulation Study on The Preparation of Skin Cosmetics

Abstract: Cosmetics have been a trend necessary for all people. The increasing need of the community in the use of cosmetics becomes the basis of the formulation of this article. Pre-formulation study for cosmetics is important to ensure that the final preparation of the cosmetics is safe to use and has maintained quality. A pre-formulation study for cosmetics is a study of physicochemical characteristics associated with the substances used in the formulation of cosmetics preparation to produce a quality cosmetic produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
1
4
0
1
Order By: Relevance
“…It was observed that the bacteria incorporated in the gel stored at 5 • C remained viable, and the gel was stable throughout the assay. The same happened in other studies, where the formulations showed better viability and stability when stored at 5 • C and 4 • C [54,55].…”
Section: Discussionsupporting
confidence: 83%
“…It was observed that the bacteria incorporated in the gel stored at 5 • C remained viable, and the gel was stable throughout the assay. The same happened in other studies, where the formulations showed better viability and stability when stored at 5 • C and 4 • C [54,55].…”
Section: Discussionsupporting
confidence: 83%
“…Hasil tersebut telah memenuhi persyaratan yaitu pH 4,5 -6,5. Persyaratan tersebut merujuk pada pH kulit manusia sehingga semua sediaan uji tidak mengiritasi kulit (Ainurofiq et al, 2021). 5,4 ± 0,00 4.00 ± 0,23 6 ± 0,02 3 : 11 1 5,5 ± 0,00 5.00 ± 0,12 5 ± 0,01 3 : 51 2 5,6 ± 0,00 6.00 ± 0,25 6 ± 0,01 4 : 02 3 5,1 ± 0,00 8.00 ± 0,15 6 ± 0,01 3 : 56 4 5,1 ± 0,00 4.00 ± 0,20 7 ± 0,02 3 : 46 5 5,3 ± 0,00 4.00 ± 0,18 5 ± 0,01 3 : 05 6 5,5 ± 0,00 5.00 ± 0,11 5 ± 0,02 3 : 31 7 5,3 ± 0,00 6.00 ± 0,17 6 ± 0,02 3 : 28…”
Section: Hasil Uji Ph Viskositas Daya Sebar Dan Waktu Kering Sediaanunclassified
“…To maintain the properties and final product of the hair shampoo, the compatibility of the active ingredients and excipients was evaluated. This is to ensure that the final product produced meets the aesthetic function, and maintains the physical and chemical properties within the preparation [22]. The physical compatibility study is essential to determine any incompatibility between the extract and excipients in the final formulation.…”
Section: Physical Compatibility Test Of Pre-formulationmentioning
confidence: 99%